The Mediating Role of Collaborative Skills on The Students’ Business Correspondence Learning Outcomes Based on The Contructivism Theory - Tusyanah Tusyanah; Rahayu Puji Haryanti; Jarot Tri Bowo Santoso; Nur Chayati; Mar'atus Sholikah (Universitas Negeri Surabaya, 2025)
This research aims to enhance students' correspondence skills by investigating the impact of collaborative skills, engagement, and interpersonal communication on learning outcomes for office administration students. This quantitative study analyzed data from 118 students using SEM-PLS and found that collaborative skills had the most significant influence, followed by engagement and interpersonal communication. The findings indicate that collaborative learning activities are an effective way to enhance communication skills and engagement in learning outcomes. Additionally, the study revealed that collaborative skills successfully mediate between interpersonal communication and engagement in correspondence learning outcomes. These insights are valuable as they demonstrate how collaborative skills, engagement, and interpersonal communication impact learning outcomes for office administration students. By highlighting the significance of collaborative learning activities, the positive correlation between engagement and academic success, and the mediating role of collaborative skills in interpersonal communication, educators can tailor curricula to better prepare students for the complexities of modern workplaces.